A Review of Robotics Research in South Africa - Boje, E.; Christopher, R.L.; Fernandes, J.; Hepworth, J.H.; Kuriakose, R.B.; Kruger, K.; Lorimer, T.; Luwes, N.; Mouton, H.D.; Patel, A.; Rosman, B.; Smit, W.J.; et al. (R & D Journal of the South African Institution of Mechanical Engineering, 2019)
Robots are increasingly being used in the industry. Businesses that use robots can produce products and provide services at lower costs and with higher quality. Some industries, like automotive manufacturing, have become dependent on robots. The impact of robots on society and the greater economy is not clear. Robots threaten the jobs of lowskilled workers and even middle-skilled workers. While researchers and governments are trying to understand the impact of robots on the economy, it is commonly accepted that robots will be used more widely across all industries. With this in mind, it is useful to consider the current research in robotics at South African research institutions. This paper is such a review. It is not exhaustive, but it provides a sense of the robotics research being done in South African research institutions. It appears that research institutions do not work on common themes, yet many research groups relate their work to Industry 4.0. The review suggests that each research group is working on topics of interest to them. The implication of this is that a wide variety of robotic themes are being researched in South Africa.
Published Article